Forecast modelling of water supply-demand for metropolitan Bangkok - Kim, Hoon; Fude I.; Shin, Hang Sik; Van Frausum, Yves G.; DAAD, Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1986)
It is very important for government to forecast future water supply and demand, in order to establish a be s t plan for Bangkok Metropolis. In urban areas, domestic, public, commercial and industrial water demands are required. Each sectoral water production and consumption are affected by several factors such as population, number of metered connections, weather and personal income . In this study three kinds of model will be introduced. They are sectoral water production model, total water production model and sectoral water consumption model. Each sectoral water production mod e l a nd consumption model are governed by different factors. The Water production and consumption models are summarized as given below.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Bangkok -- Water-supply